Analysis Of The Effect Of Personalization On Customer Experience In The Use Of Chatbot: Case Study Of Shopee E-Commerce Chatbot - Amanda Puspita Dewi; Arif Hartono (UNIVED Press, 2025)
In the rapidly evolving digital era, the use of Artificial Intelligence (AI) has been increasingly implemented across various industries, including e-commerce. The significant AI implementation is the use of the chatbots to enhance customer experience. This study aims to analyze the impact of personalization on AI-based customer experience on the Shopee e-commerce platform. Additionally, this research examines the mediating roles of trust, relationship commitment, and perceived sacrifice in the relationship between personalization and customer experience. This study use quantitative approach by collecting online survey data from Shopee users who have used the Shopee chatbot ‘Choki’. The data obtained is analyzed using the Structural Equation Modeling (SEM) method with SmartPLS. The results indicate that personalization positively influences AI-based customer experience. Furthermore, trust and relationship commitment serve as mediators that strengthen the relationship between personalization and customer experience. This study provides theoretical contributions to the development of literature on AI based customer experience and practical implications for e-commerce managers in enhancing chatbot personalization strategies to create positive customer experience and strengthen customer loyalty.